A comprehensive analysis of carotenoids metabolism in two red-fleshed mutants of Navel and Valencia sweet oranges (Citrus sinensis) - Zacarías-García, Jaime; Cronje, Paul J.; Diretto, Gianfranco; Zacarías, Lorenzo; Rodrigo, María Jesús (Frontiers in Plant Science, 2022)
Kirkwood Navel and Ruby Valencia are two spontaneous bud mutations of the respective parental lines of sweet orange (Citrus sinensis) Palmer Navel and Olinda Valencia, showing an atypical red pigmentation of the pulp. These red-fleshed varieties are commercially available and highly attractive for consumers but their carotenoid metabolism and the basis of the mutation have not been investigated. The red colour of Kirkwood and Ruby pulp was observed from the very early stages of fruit development until full maturity and associated with an altered carotenoid profiling. The red-fleshed varieties accumulated from 6- up to 1000-times more total carotenoids compared to the standard oranges. Specifically, the pulp of Kirkwood and Ruby accumulated large amounts of phytoene and phytofluene, and moderate contents of lycopene. Moreover, the red-fleshed oranges contained other unusual carotenes as -carotene, and lower concentrations of downstream products such as β,β-xanthophylls, abscisic acid (ABA) and ABA-glucosyl ester. This peculiar profile was associated with chromoplasts with lycopene crystalloid structures and round vesicles likely containing colourless carotenes. The flavedo and leaves of Kirkwood and Ruby showed minor changes in carotenoids, mainly limited to higher levels of phytoene. The carotenoid composition in Kirkwood and Ruby fruits was not explained by differences in the transcriptional profile of 26 genes related to carotenoid metabolism, covering the main steps of biosynthesis, catabolism and other processes related to carotenoid accumulation. Moreover, sequence analysis of the lycopene cyclase genes revealed no alterations in those of the red-fleshed oranges compared to the genes of the standard varieties. A striking event observed in Kirkwood and Ruby trees was the reddish coloration of the inner side of the bark tissue, with larger amounts of phytoene, accumulation of lycopene and lower ABA content. These observation lead to the conclusion that the mutation is not only manifested in fruit, affecting other carotenogenic tissues of the mutant plants, but with different consequences in the carotenoid profile. Overall, the carotenoid composition in the red-fleshed mutants suggests a partial blockage of the lycopene β-cyclization in the carotenoid pathway, rendering a high accumulation of carotenes upstream lycopene and a reduced flow to downstream xanthophylls and ABA.